Choice Feeding of Two Different Broiler Strains Using Diets with Constant Energy Level - Cerrate, S.; Coto, C.; Wang, Z.; Yan, F.; Costa, F.G.; Waldroup, P.W. (International Journal of Poultry Science, 2008)
Chicken from two broiler strains known to differ in growth rate and feed conversion (Growth) and in high breast meat yield (Yield) were grown to 10 days of age on a common starter diet and from 11-49 days were provided single diets (control) or isoenergetic choices between 15% and 24% or 15% and 32% crude protein (CP) diets. The Growth strain had greater body weight and intake of feed, protein and energy at all intervals except for 42-49 d of age as well as carcass characteristic in weight basis than did Yield strain. However, the latter strain had better feed, protein and energy conversion at 42-49 d of age and breast meat yield than did the former strain. Birds fed the isoenergetic diets varying in protein content had similar body weight, feed intake, feed conversion, energy intake, energy conversion and carcass characteristic expressed in relative term as did birds fed the control diets. Only for the last period of feeding (42-49 d of age), the protein consumption and conversion by birds fed choice of 15 and 24% CP were higher than those of birds fed the control diets. The Growth strain had a slightly greater preference for the high protein diet and consequently a higher protein intake compared to Yield strain. It seems that the selection of protein density was determined by the growth rate rather than the breast yield. There was a marked preference for the low protein diet (15% CP) over the high protein diets (24 and 32% CP), but this preference was reduced when the low protein diet was offered with the 24% CP diet. The levels of selected protein of birds given the choice diets were higher than those of control diets except for the period of 10-22 d of age and increased with age. These data indicate that these choice feeding systems can detect differences in protein requirement of two strains influenced by the growth rate.